Knowing our own minds (Mind Association occasional series, 1998)
Self-knowledge is the focus of considerable attention from philosophers: Knowing Our Own Minds gives a much-needed overview of current work on the subject, bringing together new essays by leading figures. Knowledge of one's own sensations, desires, intentions, thoughts, beliefs, and other attitudes is characteristically different from other kinds of knowledge, such as knowledge of other people's mental attributes: it has greater immediacy, authority, and salience. Together these original, stimulating, and closely interlinked essays demonstrate the special relevance of self-knowledge to a broad range of issues in epistemology, philosophy of mind, and philosophy of language.